Inhibition of phosphodiesterase: A novel therapeutic target for the treatment of mild cognitive impairment and Alzheimer’s disease - Sheng, Jianwen; Zhang, Shanjin; Wu, Lule; Kumar, Gajendra; Liao, Yuanhang; GK, Pratap; Fan, Huizhen (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is the most common form of dementia and is ranked as the 6th leading cause of death in the US. The prevalence of AD and dementia is steadily increasing and expected cases in USA is 14.8 million by 2050. Neuroinflammation and gradual neurodegeneration occurs in Alzheimer’s disease. However, existing medications has limitation to completely abolish, delay, or prevent disease progression. Phosphodiesterases (PDEs) are large family of enzymes to hydrolyze the 3’-phosphodiester links in cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) in signal-transduction pathways for generation of 5’-cyclic nucleotides. It plays vital role to orchestrate several pharmacological activities for proper cell functioning and regulating the levels of cAMP and cGMP. Several evidence has suggested that abnormal cAMP signaling is linked to cognitive problems in neurodegenerative disorders like AD. Therefore, the PDE family has become a widely accepted and multipotential therapeutic target for neurodegenerative diseases. Notably, modulation of cAMP/cGMP by phytonutrients has a huge potential for the management of AD. Natural compounds have been known to inhibit phosphodiesterase by targeting key enzymes of cGMP synthesis pathway, however, the mechanism of action and their therapeutic efficacy has not been explored extensively. Currently, few PDE inhibitors such as Vinpocetine and Nicergoline have been used for treatment of central nervous system (CNS) disorders. Considering the role of flavonoids to inhibit PDE, this review discussed the therapeutic potential of natural compounds with PDE inhibitory activity for the treatment of AD and related dementia.